Business models for airport management and development: air-side effects - Franco, Nuno Filipe Barradas (2014)
The civil aviation has always faced demanding challenges. One of the challenges of our days is the massification of its main product: air travel. The increased mobility in our society determines that, different airports, in a geographic area, compete for the same market. The airlines, their main clients, face a particularly difficult situation, also dealing with though competition and high operational costs, adding to this, the oil prices escalade may have restarted, thus guessing a difficult picture for the airlines in a near future and increased pressure over the airports’ taxation policies. The quest for success in this dynamic and competitive market has driven airports to look for revenue augmentation solutions that meet the airlines’ demands of adjustment to their favour of the traditional source of airport revenue: Airport Taxes. To tackle this and at the same time answer to many passenger comfort and quality of services demands, the solution was to go commercial. Meanwhile, advances in air traffic control technology represent a window of opportunity for a more efficient use of airport structures and airspace, therefore increasing the volume of aircraft movements possible within the same infrastructure. Many airports around the world, took advantage of the enormous passenger flow thru airport terminals, to market all kinds of services and commodities, in the airport’s premises and in the airport’s surrounding land (often airport’s property). Whether related to the aeronautical industry or not, companies, are naturally driven to seek the advantages of being located next to an airport facility, where business is alive and land prices are lower. This business model has achieved success in many airports around the world and others show signs of development in that direction, taking advantage of this new trend, in which airports make profit acting as the landlord, in what are already being called: Aerotropolis. The regional economy is animated by the presence of a prosperous and growing airport city, but regional planning must integrate the airport city adequately, specially in what concerns to it’s transportation network that will, not only, provide access but also has the potential to expand the airport’s area of influence.